The Lipid-Binding Defective Dynamin 2 Mutant in Charcot-Marie-Tooth Disease Impairs Proper Actin Bundling and Actin Organization in Glomerular Podocytes - Hamasaki, Eriko; Wakita, Natsuki; Yasuoka, Hiroki; Nagaoka, Hikaru; Morita, Masayuki; Takashima, Eizo; Uchihashi, Takayuki; Takeda, Tetsuya; Abe, Tadashi; Lee, Ji-Won; Iimura, Tadahiro; Saleem, Moin A; et al. (Frontiers in Cell and Developmental Biology, 2022)
Dynamin is an endocytic protein that functions in vesicle formation by scission of invaginated membranes. Dynamin maintains the structure of foot processes in glomerular podocytes by directly and indirectly interacting with actin filaments. However, molecular mechanisms underlying dynamin-mediated actin regulation are largely unknown. Here, biochemical and cell biological experiments were conducted to uncover how dynamin modulates interactions between membranes and actin in human podocytes (HPCs). Actin-bundling, membrane tubulating, and GTPase activities of dynamin were examined in vitro using recombinant dynamin 2-wild-type (WT) or dynamin 2-K562E, which is a mutant found in Charcot-Marie-Tooth patients. Dynamin 2-WT and dynamin 2-K562E led to the formation of prominent actin bundles with constant diameters. Whereas liposomes incubated with dynamin 2-WT resulted in tubule formation, dynamin 2-K562E reduced tubulation. Actin filaments and liposomes stimulated dynamin 2-WT GTPase activity by 6- and 20-fold, respectively. However, actin filaments, but not liposomes, stimulated dynamin 2-K562E GTPase activity by 4-fold. Self-assembly dependent GTPase activity of dynamin 2-K562E was reduced to one-third compared to that of dynamin 2-WT. Incubation of liposomes and actin with dynamin 2-WT led to the formation of thick actin bundles, which often bound to liposomes. The interaction between lipid membranes and actin bundles by dynamin 2-K562E was lower than that with dynamin 2-WT. Dynamin 2-WT partially colocalized with stress fibers and actin bundles based on double immunofluorescence of HPCs. Dynamin 2-K562E expression resulted in decreased stress fiber density and the formation of aberrant actin clusters. Dynamin 2-K562E colocalized in aberrant actin clusters with-actinin-4. Reformation of stress fibers after cytochalasin D-induced actin depolymerization and washout was less effective in dynamin 2-K562E-expressing cells than that in dynamin 2-WT. Bis-T-23, a dynamin self-assembly enhancer, was unable to rescue the decreased focal adhesion numbers and reduced stress fiber density induced by dynamin 2-K562E expression. These results suggest that the low affinity of the K562E mutant for lipid membranes, and atypical self-assembling properties, lead to actin disorganization in HPCs. Moreover, lipid-binding and self-assembly of dynamin 2 along actin filaments are required for podocyte morphology and functions. Finally, dynamin 2-mediated interactions between actin and membranes are critical for actin bundle formation in HPCs.